Mathematics Learning Strategies Based on Characteristics of Elementary School Students - Astini Ni Wayan; Rini Purwwati Ni Kadek (FPMIPA IKIP PGRI Bali, 2020)
Understanding of students as one of the teacher competencies can help determine learning strategies, as well as help determine attitudes in treating students. Each student has different characteristics and developments. Characteristics of students in elementary school (ages 6-12 years) are included in the stages of intellectual development. The stage of children's intellectual development begins when the child is able to think or reach a logical connection between impressions and make decisions about what he is connecting logically. An adequate understanding of the characteristics of elementary school students will support the success of the mathematics learning process. This article is a literature review that reviews mathematics learning strategies according to the characteristics of elementary school students.